Climate Change and Food Security Adapting Agriculture to a Warmer World - Lobell, David; Burke, Marshall; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Roughly a billion people around the world continue to live in state of chronic hunger and food insecurity. Unfortunately, efforts to improve their livelihoods must now unfold in the context of a rapidly changing climate, in which warming temperatures and changing rainfall regimes could threaten the basic productivity of the agricultural systems on which most of the world$1 (Bs poor directly depend. But whether climate change represents a minor impediment or an existential threat to development is an area of substantial controversy, with different conclusions wrought from different methodologies and based on different data. This book aims to resolve some of the controversy by exploring and comparing the different methodologies and data that scientists use to understand climate$1 (Bs effects on food security. In explains the nature of the climate threat, the ways in which crops and farmers might respond, and the potential role for public and private investment to help agriculture adapt to a warmer world. This broader understanding should prove useful to both scientists charged with quantifying climate threats, and policy-makers responsible for crucial decisions about how to respond. The book is especially suitable as a companion to an interdisciplinary undergraduate or graduate level class. "This book provides a much needed analysis of the interactions between climate change and the food system, with emphasis on how food security is likely to be affected and interventions needed to adapt to a warmer world." Per Pinstrup-Andersen, Cornell University, New York, USA.s
I -- Climate Effects on Food Security: An Overview -- Climate Models and Their Projections of Future Changes -- II -- Crop Response to Climate: Ecophysiological Models -- Crop Responses to Climate: Time-Series Models -- Crop Responses to Climate and Weather: Cross-Section and Panel Models -- Direct Effects of Rising Atmospheric Carbon Dioxide and Ozone on Crop Yields -- III -- Food Security and Adaptation to Climate Change: What Do We Know? -- Breeding Strategies to Adapt Crops to a Changing Climate -- IV -- Global and Regional Assessments -- Where Do We Go from Here? -- Erratum.
Keywords: Environment; Climate change; Earth sciences; Agriculture; Sustainable development; Environment; Climate Change; Sustainable Development; Agriculture; Climate Change Management and Policy; Earth Sciences, general; Electronic books